Economic and financial impact of corporate sustainability on sustainable competitive advantage - Pimenta, Daiana Paula (2015)
The balance between environmentally sustainable, socially ethical and economic growth has been investigated in the literature of business strategy. However, studies do not show whether or not a for-profit organization can gain sustainable competitive advantage. Some limitations refer to non-experimental studies that do not control spurious effect of confounding variables, as well as not using variables that capture the intangible aspects of sustainable practices. To overcome these limitations, this study examined whether adherence to corporate sustainability practices - the company's presence in the Corporate Sustainability Index (CSI) - is itself a source of sustainable competitive advantage, controlling spurious effects. By means of experimental design using control group, we used Generalized Estimation Equations with dependent variables Tobin's Q, Return on Assets and Financial Leverage and, as control, firm size, industry, and year of data collection. The results indicate that participation in the CSI does not affect the degree of leverage of firms, but positively influences the return on assets and the market value above the average of other compa-nies in the same industry throughout the years. Thus, sustainable practices bring financial benefits above the average of other companies in the same industry throughout the years, making them a sustainable competitive advantage